Pilot-Less Time Synchronization for OFDM Systems: Application to Power Line Receivers. (12th January 2016) - Lalos, Aris S.; Vgenis, Athanasios; Gioulekas, Fotios; Birbas, Michael
Abstract : Power line networks provide high-speed broadband communications without the need for new wirings. However, these networks present a hostile environment for high-speed data communications. The most common modulation method used in such systems is OFDM, since it copes effectively with noise, multipath, fading selectivity, and attenuation. A potential drawback of OFDM is its sensitivity to receiver synchronization imperfections, such as timing and sampling frequency offsets. Although several approaches have been proposed for estimating the time and frequency offset, they are based on the use of pilot sequences that are not available in power line communication standards. More importantly, they focus on isolated algorithms for compensating either time or frequency offsets without providing a complete, low complexity, OFDM receiver architecture that mitigates jointly time and frequency errors. This paper focuses on providing an OFDM receiver architecture that can be compatible with many power line standards. Extensive simulation studies show under realistic channel and noise conditions that the proposed receiver provides enhanced robustness to synchronization imperfections as compared to conventional approaches.